Gender-based differences in career paths, parenthood and perspectives on professional barriers among Asian ophthalmologists - Claire L Peterson; Brian S.Y. Yeo; Shelley Yin-Hsi Chang; Rachel S Chong; Marcus Ang; Anna CS Tan; Tina Wong; Andrew S.H. Tsai (AJO International)
Background: Gender equality in Asia remains under-researched, especially within medical fields. This study explored gender-related differences among ophthalmologists in Asia. Design: Observational, cross-sectional survey study. Methods: An anonymous online survey was distributed across 21 Asian regions via the Young Ophthalmologist network (June–July 2024), examining career paths, leadership, research, parenthood and gender-related workplace experiences. Results: A total of 242 cisgendered ophthalmologists from 20 regions responded; 163(67%) identified as women. Although most institutions had gender-balanced workforces, gender disparities persisted. Men were more likely than women to pursue surgically-oriented subspecialties such as surgical retina and cornea (M83% VS W52%, p=0.02). Women reported a greater impact on parenthood on subspecialty choice (W54% vs M28%, p<0.001) and career progression (W64% vs M39%, p<0.001). Women were also more likely to work part-time due to family commitments.While overall leadership, academic positions and research output were similar, head of department roles in particular were predominantly held by men (62%), with women perceiving they had less opportunities in leadership (W61% vs M90%, p<0.001) and research (W80%, M93%, p=0.01) compared to their male counterparts, and reporting a need to champion women in these areas. Women also experienced more gender discrimination and sexual harassment from their patients, colleagues, and bosses of the opposite sex compared to men(p<0.05). Conclusion: Women contribute significantly to ophthalmology in Asia but gender-related disparities remain for subspecialty choice, perceived leadership and research opportunities, parenthood, discrimination and harassment. Addressing these through mentorship, education, flexible career support, advocacy and institutional reform is essential to achieving gender equity in all areas of ophthalmology.